Credit Reporting at the Base of the Pyramid : Key Issues and Success Factors - Lyman, Timothy; Lythgoe, Tony; Miller, Margaret; Reille, Xavier; Sankaranarayan, Shalini (International Finance Corporation and CGAP, Washington, DC, 2017)
Over the past five years, the microcredit sector has experienced unprecedented growth. The number of borrowers served by microfinance institutions (MFIs) has increased threefold to reach 120 million clients, according to MIX estimates as of December 2009 and by other estimates the number may be as high 190 million (Microcredit Summit Campaign 2011). In large markets, such as Mexico and South Africa, commercial banks and consumer lending companies have expanded their activities to include microfinance for low-income households. Unfortunately, the growth of microcredit is not always sustainable. Some iconic markets, such as India and Bosnia Herzegovina, are experiencing large-scale credit crises, and they are not alone. The deterioration in the quality of MFI loan portfolios can be attributed to several factors. Some fast growing MFIs have outgrown their risk management systems and controls. These weaknesses have often been exacerbated by high staff turnover, leading to a further erosion of credit discipline. Rapid growth has also been focused in narrow geographies, which in turn affected borrower repayment incentives and behaviors. This report takes a fresh look at the state of credit reporting at the base of the pyramid. The data and analysis for this paper are drawn from International Finance Corporation (IFC) and Consultative Group to Assist the Poorest (CGAP) market intelligence on credit reporting systems. the lessons learned for effective credit reporting at the base of the pyramid and identifies key success factors as well as common challenges.